Sistem Pendukung Keputusan Pemilihan Rumah Kos untuk Mahasiswa di Rantauprapat Menggunakan Metode SAW - Vinna Olymphyani; Anggi Putri Khatami Simbolon; Gilang Kurnia Rambe; Ridwan Hafiz Ritonga (Journal of Science, Technology, and Innovation, 2026)
Selecting a boarding house is a critical issue for students living away from home, as it involves various multi-criteria considerations—such as location, price, facilities, and security—that are often difficult to evaluate objectively using conventional approaches. This study aims to design and implement a Decision Support System for selecting student boarding houses in Rantauprapat using the Simple Additive Weighting (SAW) method. The study employs an empirical approach based on system development through the following stages: user needs identification, determination of criterion weights, formation of a decision matrix, data normalization, and calculation of preference values to generate a ranking of student housing alternatives. The results indicate that the SAW method effectively integrates cost and benefit attributes systematically, thereby producing objective and consistent recommendations for student housing. The validation process demonstrated consistency between manual calculations and system outputs, while effectiveness testing revealed high user satisfaction regarding the accuracy of recommendations and the efficiency of data processing. The developed system is deemed capable of supporting students’ decision-making processes more quickly, transparently, and adaptively to user needs.